2021
DOI: 10.1093/biostatistics/kxab047
|View full text |Cite
|
Sign up to set email alerts
|

Integrated causal-predictive machine learning models for tropical cyclone epidemiology

Abstract: Summary Strategic preparedness reduces the adverse health impacts of hurricanes and tropical storms, referred to collectively as tropical cyclones (TCs), but its protective impact could be enhanced by a more comprehensive and rigorous characterization of TC epidemiology. To generate the insights and tools necessary for high-precision TC preparedness, we introduce a machine learning approach that standardizes estimation of historic TC health impacts, discovers common patterns and sources of heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…These studies also utilized a wind field model to quantify the TC exposure for a large number of TCs and found an elevated risk of mortality [ 9 , 27 ], hospitalization [ 10 , 11 ], and preterm birth [ 26 ] associated with TCs in the USA for the past decades. To our knowledge, only 1 study has estimated the TC-specific health risks, which included all TCs in the USA from 1999 to 2015 and also observed large variations in the TC-related excess mortality across and within TCs [ 27 ]. However, this study did not estimate the TC-specific POC, but instead used an 11-day post-TC period as a hypothetical POC and calculated the excess deaths within this period for all TCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies also utilized a wind field model to quantify the TC exposure for a large number of TCs and found an elevated risk of mortality [ 9 , 27 ], hospitalization [ 10 , 11 ], and preterm birth [ 26 ] associated with TCs in the USA for the past decades. To our knowledge, only 1 study has estimated the TC-specific health risks, which included all TCs in the USA from 1999 to 2015 and also observed large variations in the TC-related excess mortality across and within TCs [ 27 ]. However, this study did not estimate the TC-specific POC, but instead used an 11-day post-TC period as a hypothetical POC and calculated the excess deaths within this period for all TCs.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an overall monotonically increasing, non-threshold and approximately linear curve of TC-related maximum sustained windspeed and cumulative rainfall with all-cause, cardiovascular, and respiratory mortality risks. Only 1 prior study has estimated the ER curves of TC characteristics with health outcomes and observed a similar monotonically increasing ER relationship with an approximately linear shape between TC-related maximum sustained windspeed and all-cause mortality, hospitalizations for respiratory diseases, chronic obstructive pulmonary diseases, and cardiovascular diseases in the USA [ 27 ]. Stronger TCs with higher windspeed and rainfall were more likely to induce adverse events such as flood, displacement and power outage, there having higher risks causing mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is a limitation in future work focused on understanding the mechanistic pathway linking CVD and hurricanes, novel, validated causal inference methods that allow identification are now available, making this work possible. 76 Future research should seek to use these tools and large data sources to develop an understanding of potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Furthermore, several recent important studies on the associations of cyclones with health were published after these reviews. 7 , 13 15 , 17 , 22 , 32 …”
Section: Introductionmentioning
confidence: 99%